2008
DOI: 10.2174/1874440000802010065
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol Intoxication on Neuronal Activation at Different Levels of Cognitive Load

Abstract: Abstract:The aim of this study was to investigate how alcohol intoxication at two blood alcohol concentrations (BAC) affected neuronal activation during increasing levels of cognitive load. For this purpose we used functional magnetic resonance imaging (fMRI) together with a working memory n-back paradigm with three levels of difficulty. Twenty-five healthy male participants were scanned twice on two separate days. Participants in the control group (N=13) were scanned after drinking a soft-drink at both scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
(33 reference statements)
3
17
0
Order By: Relevance
“…Gundersen and colleagues (2008) observed decreased activation in ACC and cerebellum during a working memory task under a moderate alcohol dose. A slightly lower alcohol dose and a different variant of a working memory task resulted in increased activation in dlPFC and decreased activation in parietal regions (Paulus, et al 2006).…”
Section: Introductionmentioning
confidence: 83%
“…Gundersen and colleagues (2008) observed decreased activation in ACC and cerebellum during a working memory task under a moderate alcohol dose. A slightly lower alcohol dose and a different variant of a working memory task resulted in increased activation in dlPFC and decreased activation in parietal regions (Paulus, et al 2006).…”
Section: Introductionmentioning
confidence: 83%
“…While substantial spurious intersubject variability is possible in a general fMRI experiment, the experimental design and post-processing procedures employed here specifically controlled for these factors. For instance, several studies have shown the N-back task to be generally insensitive to drug use, except in cases of overt intoxication (Gundersen et al, 2008a; Table 2 Summary statistics for the distribution of number and peak linear magnitude of the recorded impacts for the three injury groups. The distributions of peak linear magnitude do not significantly differ (Kruskal-Wallis, w 2 ¼1.28, p4 0.52); however, the distributions of the number of blows sustained are significantly different (KruskalWallis, w 2 ¼ 6.1, p o 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Previous fMRI studies have shown the modulation of neuronal activation following acute alcohol ingestion in various types of crossover activation design with experimental tasks. These included auditory (Seifritz et al, 2000) and visual perception tasks (Calhoun et al, 2004a;Levin et al, 1998), goal-directed visuo-motor (Van Horn et al, 2006 and memory (Gundersen et al, 2008) tasks and even more complex scenarios like simulated driving (Allen et al, 2009;Calhoun et al, 2004b;Meda et al, 2009). Although previous studies have been extremely informative for visualizing alcohol effects on brain functionality and illustrating important implications of fMRI after drug administration, it has remained difficult in conventional task-based fMRI studies to determine whether differences in activation and taskby-drug interactions were due to a directly drug-affected brain function or to an altered behavioral performance secondary to an altered baseline state of the brain due to drug administration.…”
Section: Discussionmentioning
confidence: 99%